The US department of labor's final "fiduciary" rule incorporates concessions to financial service industry but still poses key challenges. Issue 4 (7th November 2016) - Laverierre, Kenneth J.; Behrens, Matthew H.
Abstract : Purpose: To describe the main provisions of the US Department of Labor's final "fiduciary" rule and its related prohibited transaction exemptions and the key challenges the rule poses for financial advisers. Design/methodology/approach: This article describes the impact of the new "fiduciary" rule on broker-dealers, banks and other financial organizations who will, for the first time since the passage of ERISA, be subject to ERISA's fiduciary standards and remedies when providing investment and asset management recommendations to individual retirement accounts and other retail retirement clients. Findings: The most immediate impact of the rule will be on the compensation practices at broker-dealers and other financial institutions and on the fee and revenue sharing arrangements among funds, fund sponsors and the financial institutions that offer investment advice to retail retirement clients. Although the new rule responds to many of the concerns raised by the financial services industry, compliance with the rule will require the restructuring of pay and compliance policies at financial institutions servicing retail clients. Originality/value: Practical guidance from experienced ERISA lawyers.